Development and performance evaluation of an aquaponic system - ASWATHI P. V; Athul Krishna M. M; Mohammad Suhail; Kurias Thomas; Dr. Sasikala D (Guide) (Tavanur 2016 Department of Irrigation & Drainage Engineering)
Development and performance evaluation of an aquaponic system
Development and performance evaluation of an aquaponic system
Keywords: Aquaponics system/ Hydroponics/ Aquaculture elements